Pillars of the System of ius matrimoniale canonicum According to Remigiusz Sobański - Pastwa, Andrzej (Philosophy and Canon Law, 2022)
“The Gaudium et spes Constitution does not approach [matrimony] a priori—as the Casti connubii Encyclical did—but, instead, it analyzes the reality of matrimony as it is reflected in the Christian consciousness shaped by the teaching of the Church.” This characteristic sentence, derived from Śląskie Studia Historyczno-Teologiczne [Silesian Studies in History and Theology] (1968), which debuted at that time on the market of theological periodicals, shows in itself the epistemological sensitivity and sharp methodical sense of the Author and the Executive Editor of the periodical. This study adopts a hypothesis, which suggests that in this and similar lines of the famous article from 1969—perfectly set in the current of the conciliar aggiornamento—a key to understanding the phenomenon and scientific format of the work of Rev. Professor Remigiusz Sobański (1930–2010) appeared. Positive verification of this hypothesis is not in doubt: the experience of half a century of work as a scientist and person with real-life experience (a judge and officials in the Katowice Tribunal) and the related fact that he has become an undisputed authority in the field of canonical matrimonial law, resulted in the Author’s exposition of the systemic principles of the codified ius matrimoniale (CIC 1983). This finding makes it necessary to reflect, with sharpened attention, on the title area “Pillars of the system of ius matrimoniale canonicum according to Remigiusz Sobański” in the following order: (1) “the principle of matrimonial indissolubility” (irrevocabilis consensus personalis—vinculum indissolubile), (2) “the principle [that] shapes from within all the canonical norms on marriage” (favor matrimonii), (3) “the principle of the right to marriage” (ius connubii), (4) “sacrament— one of the structural elements of the Church” (sacramentum matrimoni; principles: eo ipso sacramentum and favor fidei).